Water resource management in India - Vajpeyi, Dhirendra (1999)
Following an analysis of the factors responsible for problems relating to water in developing nations in general, including India, the author focuses on water management scenario in the country. Besides discussing grim ground realities, he covers institutional framework, national policy, recommendations of commissions/committees, National Water Board, and the need for a sustainable action plan, operationalisation of "polluter pays" principle with supportive legal administrative framework, and participation of beneficiaries for securing functioning of a sound strategy on our critical water front. - Reproduced
Keywords: Water resources management - India; Water resources management